How can I show that below equation holds ?

$\int\limits_{0}^{t} f \left( s \right)W_s ds = W_t \int\limits_{0}^{t}f \left( s \right)ds - \int\limits_{0}^{t}\int\limits_{0}^{s} f\left( u \right)dudW_s $

$W_t$ is regular Wiener process.


2 Answers 2



$$g_s = \int_0^s f_u du$$

By Ito-Leibniz product rule:

$$ d(W_sg_s) = W_sdg_s+ g_sdW_s +d[g,W]_s $$

Assuming $f_s$ is deterministic, $d[g,W]_s = 0$ and we get:

$$ d(W_sg_s) = W_sdg_s + g_sdW_s $$ In integral form, this is:

$$ W_tg_t = \int_0^t W_sdg_s + \int_0^t g_sdW_s $$

Getting back to $f$:

$$ W_t \int_0^t f_u du = \int_0^t W_sf_sds + \int_0^t \int_0^s f_u du dW_s $$

  • $\begingroup$ Should be $d g_s$ after the Ito leibniz rule. $\endgroup$
    – oliversm
    Aug 2, 2020 at 13:04
  • $\begingroup$ @oliversm fixed it. thank you. $\endgroup$
    – ir7
    Aug 2, 2020 at 13:14

We can use Stochastic Integration by Parts to show this.

Taking the corollary from the link above \begin{align} X_t Y_t = X_0 Y_0 + \int_0^t X_s dY_s + \int_0 ^t Y_{s-} dX_s \end{align}

We set $X_t$ and $Y_t$ equal to the following: \begin{align} X_t &\to \int_0^t f(u) du\\ Y_t &\to W_t \end{align}

then \begin{align} W_t \int_0^t f(u) du &= W_0 \int_0^0 f(u) du + \int_0^t \Bigl( \int_0^s f(u) du \Bigr) dW_s + \int_0^t W_s d\Bigl( \int_0^s f(u) du \Bigr)\\ \end{align}

The second term is $0$ (since the integration range is $0$ and $W_0 = 0$). The fourth term simplifies via the Fundamental Theorem of Calculus which says $d\Bigl( \int_0^s f(u) du \Bigr) = f(s)ds\\\\$, so: \begin{align} W_t \int_0^t f(u) du &= \int_0^t \int_0^s f(u) du dW_s + \int_0^t W_s f(s)ds\\ \int_0^t W_s f(s)ds &= W_t \int_0^t f(u) du - \int_0^t \Bigl( \int_0^s f(u) du \Bigr) dW_s \end{align}

which is the expression in your question.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.